GRADUATE EVALUATION ... NEED FOR A CHANGE - Anwar, Muhammad Shamim (Journal of Ayub Medical College Abbottabad, 2007)
After a ward round on a very busy emergency day when I entered my office the ward clerk dropped two huge postal packets wrapped in thick cloth, tightly sewed-up by some master tailor and covered with thick official seals. For a moment I could feel my heart thump inside my chest, my mouth became dry and I had a sticky feel in my throat. These were MBBS descriptive essay scripts from the university sent for checking. The bundles were capable of giving a prolapsed disc to a robust young man if he tried to be brave and pick them up. I was therefore not going to try. The accompanying letter said: